Students' Perception in Writing Essays by Using Chat GPT, Students of the Islamic Education Department, IAI Al-Khairat, Pamekasan - Santoso, Budi; Alfiansyah, Alfiansyah (Molang: Journal Islamic Education, 2025)
This study explores students' reflective and selective use of Chatgpt in academic essay writing in Islamic-based higher education. Using a qualitative approach of the phenomenological type, this study aims to understand students' experiences and perceptions of the integration of generative artificial intelligence technology in scientific writing practices. The research was conducted at the Islamic Education Study Program of IAI Al-Khairat Pamekasan, with informants purposively selected based on certain criteria: active students who have used Chatgpt at least twice in essay writing, and are willing to be interviewed openly. Data was collected through semi-structured in-depth interviews, observation of Chatgpt usage patterns, and document analysis in student essays. Data analysis was carried out through the stages of reduction, presentation, and conclusion drawing, with validation using data triangulation and confirmation to informants (member checking). The results showed that students positioned Chatgpt as a cognitive tool in initiating ideas and structuring writing, not as a substitute for academic thinking. Although it facilitates initial drafting, Chatgpt's output is general and less contextualised, especially in integrating Islamic values. Students overcame this by adding references from the Qur'an, hadith, and classical Islamic literature. In terms of ethics, students showed awareness of the potential for plagiarism and tried to maintain academic integrity through processing and re-understanding the AI results. The technology also affected confidence in writing, both positively and negatively. This study emphasises the importance of a balance between the use of technology and strengthening value-based academic literacy in an Islamic educational environment.